The influence of drying temperature variation on the quality of bagasse bio-pellet - Mohammad Jufri; Billy Muhammad; Mulyono; Daryono; Heni Hendaryati; Ali Saifullah (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2023)
Demand for bio-pellet as alternative energy has widely increased. It occurs as people are aware of energy-saving for today and future living. Therefore, the increment in bio-pellet quality has also been a concern. The bio-pellet quality can be influenced by the materials (biomass) and its treatments. One of the treatments for the bagasse bio-pellet is drying. It is conducted to lessen its moisture before it is produced by the ring die pellet mill. The influence of drying temperature on bagasse bio-pellet quality is the focus of this experiment. The result shows that the different drying temperature for bagasse bio-pellet gives a different quality. However, those qualities comply with the requirement of the Indonesian National Standard for biomass energy.